Fish Bones and English Food History - Locker, Alison (Petits Propos Culinaires, 2002)
The article explores what assemblages of fish bones, as one form of organic remains, can tell us about past diets.  Such assemblages often form an important part of finds on archaeological sites.  The author explores the processes used to identify, examine, interpret and preserve this evidence presenting examples from British sites.